Evaluation Report on Impact of Fishing Harbour Projects on the Living Conditions of Traditional Fishermen (1993-94) - Planning Commission (Planning Commission, 1994)
At the instance of the Planning Commission, the Programme Evaluation Organisation (PEO) undertook the study of the impact of fishing harbour projects on the living conditions of traditional fishermen to assess the impact in terms of employment, income, indebtedness, health, social status, examine changes relating to fishing frequency, quantity and quality of fish catch by traditional fishermen; ascertain the extent to which the facilities created at the fishing harbours fish landing centres were availed by the traditional fishermen; and identify the problems faced by them who were evacuated from the project area including that of their rehabilitation.
Programme Evaluation Organisation Planning Commission Government of India New Delhi